Higher in status, (Even) better-than-average - Varnum, Michael E. W. (Frontiers in Psychology, 2015)
In 5 studies (total N = 1357) conducted online using Amazon’s MTurk the relationship between socioeconomic status (SES) and the better-than-average effect (BTAE) was tested. Across the studies subjective measures of SES were positively correlated with magnitude of BTAE. Effects of objective measures (income and education) were weaker and less consistent. Measures of childhood SES (both objective and subjective) were positively correlated with BTAE magnitude, though less strongly and less consistently than measures of current subjective SES. Meta-analysis revealed all measures of chronic SES (with the exception of education) were significantly correlated with BTAE. However, manipulations of SES in terms of subjective status (Study 2), power (Study 3), and dominance (Study 4) did not have strong effects on BTAE magnitude (d’s ranging from -.04 - .14). Taken together the results suggest that chronic, but not temporary, status may be linked with a stronger tendency to overestimate one’s abilities and positive traits.